Beyond genetics: integrative oncology and the metabolic perspective on cancer treatment - MK Nair, Pradeep; Silwal, Karishma; Ramalakshmi, Renganathan; Devibala, Muniappan; Saranya, Maruthanayagam; Sivaranjani, Sekar; Ramasamy, Thangavelu; Palanisamy, Ayyappan; Mahalingam, Manickam (Frontiers in Oncology, 2024)
Cancer is traditionally approached as a genetic disease, with standard treatments including chemotherapy, radiation, targeted therapy, immunotherapy, and surgery significantly improving survival rates and patient outcomes. However, there is a growing recognition of the need for integrative oncology, which expands cancer management by considering cancer as a metabolic disease. Integrative medicine physicians employ holistic therapies focused on patients’ needs, aiming to correct the metabolic imbalances associated with cancer and alleviate cancer-related symptoms. Viewing cancer as a metabolic disease involves addressing factors such as an acidic microenvironment, vitamin C deficiency, mitochondrial dysfunction, reduced intracellular oxygen levels, elevated oxidative stress, dysfunctional autophagy, and psychological stress. This paper presents an overview of the evidence and comprehensive strategies supporting integrative medicine approaches in addressing cancer metabolism in integrative oncology settings. Furthermore, the paper underscores the necessity of integrating different cancer theories—genetic and metabolic—for improved patient outcomes and experiences. By combining these perspectives, integrative oncology offers a more holistic, patient-centered approach to cancer treatment.